2010
DOI: 10.3762/bjoc.6.105
|View full text |Cite
|
Sign up to set email alerts
|

Formation of epoxide-amine oligo-adducts as OH-functionalized initiators for the ring-opening polymerization of ε-caprolactone

Abstract: SummaryEpoxide-amine oligo-adducts were synthesized via a one-pot microwave assisted heterogeneous catalytic transfer hydrogenation. Accordingly, 4-nitroanisole was reduced under microwave conditions to give 4-aminoanisole which reacted immediately with the diglycidyl ether of bisphenol A in an addition polymerization reaction to yield oligo(amino alcohol)s. The hydroxy groups of the new formed oligomers were used as the initiator for the ring-opening polymerization of ε-caprolactone to produce a graft copolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…We have employed ring-opening polymerization between diglycidyl ethers (diepoxides) and polyamines 31-34 for the formation of combinatorial polymer libraries for transgene delivery35,36. Recently, it was found that a polymer 1,4 C-1,4 Bis, generated in our laboratory from 1,4-cyclohexanedimethanol diglycidyl ether (1,4C) and 1,4-bis(3-aminopropyl) piperazine) (1,4Bis) monomers demonstrated higher transgene expression than 25 kDa PEI at certain polymer:DNA weight ratios 36,37.…”
Section: Introductionmentioning
confidence: 99%
“…We have employed ring-opening polymerization between diglycidyl ethers (diepoxides) and polyamines 31-34 for the formation of combinatorial polymer libraries for transgene delivery35,36. Recently, it was found that a polymer 1,4 C-1,4 Bis, generated in our laboratory from 1,4-cyclohexanedimethanol diglycidyl ether (1,4C) and 1,4-bis(3-aminopropyl) piperazine) (1,4Bis) monomers demonstrated higher transgene expression than 25 kDa PEI at certain polymer:DNA weight ratios 36,37.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, 1-methyl-1-cyclohexene has been used as a source of hydrogen with the obvious advantage of producing the safer toluene as the oxidized product. MW-assisted Pd/C-catalyzed reduction of aromatic nitro groups [84] and nitrile in 4-(2,3-epoxypropyl-1-oxy)benzonitrile, 108, took place in good yields using 1-methyl-1-cyclohexene as a H2 donor (Scheme 31) [85]. Cyclohexene has also been used as hydrogen donor in the reduction of the nitro derivative 110, a key intermediate in the synthesis of the powerful canonical transient receptor potential channel (TRPC) inhibitor Pyr3, 112 (Scheme 32) [86].…”
Section: Other Hydrogen Sourcesmentioning
confidence: 99%
“…Diglycidyl ether can be differentiated from other organic compounds by the presence of two terminal oxirane groups, which are able to react with compounds possessing active hydrogen atoms, including amines [ 1 ], amides or mercaptans [ 2 ] and alcohols [ 3 , 4 ]. Glycidyl ethers have been widely used since the late 1940s as basic components of epoxy resins [ 5 ].…”
Section: Introductionmentioning
confidence: 99%